[OP.1B.04] CAFFEINE INTAKE AND ABSTRACT REASONING AMONG 1, 374 UNSELECTED MEN AND WOMEN FROM GENERAL POPULATION. ROLE OF THE –163C>A POLYMORPHISM OF CYP1A2 GENE. (September 2017) - Albertini, F.; Tikhonoff, V.; Favaro, J.; Montagnana, M.; Danese, E.; Finatti, F.; Benati, M.; Mazza, A.; Dal Maso, L.; Spinella, P.; Palatini, P.; Casiglia, E.
Abstract : Objective: Caffeine is considered to be an enhancer of cognitive performance but its neuroactive effects, particularly those on abstract reasoning, have never been studied in an epidemiological setting, especially in relation to the different genotypes of −163C>A polymorphism of CYP1A2 gene, largely controlling caffeine metabolism. Aim of this study was to ascertain whether free chronic caffeine intake modifies abstract reasoning in a dose-dependent manner, and if this effect is influenced by the above-mentioned polymorphism or modified by other factors. Design and method: We studied 1, 374 unselected men and women aged 51 ± 15 years (range 18 to 89) from general population. From a 7-day dietary diary, caffeine deriving from coffee, tea, chocolate or cola was calculated and summed up. Abstract reasoning was measured in the frame of a neuropsychological assessment as the ability to find a concept linking two words indicating objects or actions and explaining how they were connected. Results: In age-schooling-adjusted linear regression, the higher the caffeine intake, the better the abstraction score; the interaction term between caffeine and the −163C>A polymorphism was accepted in linear regression (coefficient 0.0012, standard error 0.0005, p = 0.002). More precisely, abstract reasoning depended on caffeine in the CC homozygous only ("slow" caffeine metabolizers), where it was higher in the 3rd tertile of caffeine intake (Figure 1). Actually, the CC homozygous in the highest tertile were as abstractive as the A-carriers ("fast" caffeine metabolizers, likely prone to consume more caffeine a day in order to avoid abstinence). Figure. No caption available. Conclusions: A direct association between caffeine intake and abstract reasoning exists in general population and is influenced by the −163C>A polymorphism, caffeine intake being the intermediate phenotype; age and ethanol reduce while smoking and schooling enhance this association.